2018
DOI: 10.1055/s-0038-1627445
|View full text |Cite
|
Sign up to set email alerts
|

Operative Time and Flap Failure in Unilateral and Bilateral Free Flap Breast Reconstruction

Abstract: Bilateral free flap breast reconstruction can be performed safely despite an increase in operative time when compared with unilateral reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 22 publications
(16 reference statements)
0
21
0
Order By: Relevance
“…Our results showed that odds of UR, eLOS, donor-site complications, medical complications, flap-site complications, fat necrosis, blood transfusion, flap compromise, and flap loss significantly increase per hour of OT in DIEP flap reconstructions, supporting the findings of previous free flap literature. 2,22,24,25,28–30 Although eLOS is significantly associated with both per hour and OT intervals, our results suggest that postoperative morbidity and UR with DIEP flap reconstructions increases per hour of OT rather than OT intervals after adjusting for intraoperative, perforator, and demographic variables. Overall, it appears OT per hour is a more universal predictor of adverse postoperative outcomes (ie, eLOS, UR, and complication occurrence) compared to OT cutoffs and intervals.…”
Section: Discussionmentioning
confidence: 63%
“…Our results showed that odds of UR, eLOS, donor-site complications, medical complications, flap-site complications, fat necrosis, blood transfusion, flap compromise, and flap loss significantly increase per hour of OT in DIEP flap reconstructions, supporting the findings of previous free flap literature. 2,22,24,25,28–30 Although eLOS is significantly associated with both per hour and OT intervals, our results suggest that postoperative morbidity and UR with DIEP flap reconstructions increases per hour of OT rather than OT intervals after adjusting for intraoperative, perforator, and demographic variables. Overall, it appears OT per hour is a more universal predictor of adverse postoperative outcomes (ie, eLOS, UR, and complication occurrence) compared to OT cutoffs and intervals.…”
Section: Discussionmentioning
confidence: 63%
“…Covariates for this model included age, race, body mass index (BMI), diabetes, hypertension, ASA classification, and laterality of reconstruction. 15 All analyses were performed using R 4.2.1 (R Foundation, Vienna, Austria) and the p-value for statistical significance was set at p < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Covariates for this model included age, race, body mass index (BMI), diabetes, hypertension, ASA classification, and laterality of reconstruction. 15 All analyses were performed using R 4.2.1 (R reconstructive options. Our data suggests that DIBR and DBR are associated with less overall complications than IBR.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on free flap breast reconstruction showed that DM was not a significant predictor of flap failure. [30] Despite the conflicting results found in various studies, DM remains a concern for surgeons. This is because it is associated with other surgical and medical complications such as bleeding, postoperative ventilation > 48 hours, and pneumonia.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…Another result of breast reconstruction with bilateral free flaps did not find a significant relationship with failure compared to unilateral free flaps even though the operating time was longer. [42] Surgical time has not been reported to be associated with an increase in overall complications (early or late) in free flap breast reconstruction. [43] Gürlek et al wrote that flap loss was not found to be significantly different between groups with ischemic time less than and more than 3 hours in head neck and breast reconstruction in Texas.…”
Section: Operation Durationmentioning
confidence: 99%